Barriers to implementing contingency management at a methadone treatment clinic: A qualitative study at a tertiary hospital in Tanzania - Paul S. Lawala; Christopher F. Akiba; Damali L. Kabwali; Liness A. Ndelwa; Betuna E. Mwamboneke; Albino Kalolo (PLoS ONE, 2025)
Introduction Contingency management in addiction behaviors has been widely applied in high income settings. Contingency management entails modification of behavior via the control or manipulation of consequences (contingencies) to the behavior. While a need exists for contingency management in low- and middle- income settings, specifically those of the sub-Saharan Africa region, uptake is low relative to high income settings. This study assessed barriers to implementation of contingency management for methadone treatment clients at the outpatient clinic of a tertiary hospital in Tanzania. Methods This study employed a qualitative design and was conducted at Mbeya Zonal Referral Hospital (MZRH). Guided by the consolidated framework of implementation research (CFIR), data were collected from two sources 1) ten purposively selected key informants (health care workers, methadone treatment clients and hospital leaders) who participated in in-depth interviews, and 2) a mini focus group discussion with five participants (two health care providers, two hospital leaders and one leader of methadone treatment clients). We developed semi-structured guides for in-depth interviews and the mini focus group to explore the key barriers. We analyzed the collected data using thematic analysis. Results Reported barriers revolved around the following key themes: lack of awareness and knowledge regarding contingency management, financial constraints to support implementation, trust between clients and health care workers, Health care workers work load, client behaviors and clinic culture. Participants mentioned lack of awareness and knowledge more frequently compared to other themes. Conclusion In the context of specialized outpatient care in Tanzania, contingency management faces a variety of barriers. Deliberate efforts to establish and sustain contingency management in these settings require strategies that attend to the identified barriers. If the barriers are overcome, contingency management implementation and sustainment may follow and ultimately improve methadone related health outcome for patients.